Comparison of Translation Techniques Between Human and Microsoft Translator (Windows 11) in Translating Folklores - Br Karosekali, Stephani Caludia; Sipayung, Kammer Tuahman; Saragi, Christina Natalina (Visi Sosial Humaniora, 2024)
The purpose of this study is to describe the comparison of folklore translation techniques performed by human and Microsoft translator (windows 11). This research was conducted using Descriptive Qualitative method. The research subjects were taken from folklores titled "Ki Ageng Gribig" and "Wendit" in "Little Sunshine Bilingual Book" translated by Lestiono et al (Human translator) and Microsoft translators (Windows 11). The object of this research is the translation techniques found in the translation results between human translators and Microsoft translators (Windows 11).The result of this study is that in translating the folklores entitled "Ki Ageng Gribig" and "Wendit", human translators and Microsoft translators (Windows 11) used several translation techniques. The human translator used eleven translation techniques, namely adaptation (6 data), amplification (9 data), description (5 data), Establised equivalent (4 data), generalization (1 data), linguistic amplification (2 data), linguistic compression (3 data), literal (16 data), modulation (17 data), reduction (31 data), transposition (2 data). Meanwhile, Microsoft translator (Windows 11) used eight translation techniques, namely adaptation (4 data), borrowing (1 data), Calque (1), description (1 data), Establised equivalent (2 data), literal (86 data), modulation (3 data), reduction (1 data).